Skin benefits of moisturising body wash formulas for children with atopic dermatitis: A randomised controlled clinical study in China. (11th September 2019) - Xu, Zigang; Liu, Xiaoyan; Niu, Yueqing; Shen, Chunping; Heminger, Kate; Moulton, Laurie; Yu, Amy; Allen, Tina; Zhang, Lesheng; Yue, Feng; Liu, Jiquan; Xu, Ying; et al.
Abstract: Background: It acknowledged that skin care is an important part of atopic dermatitis therapy. However, clinical evidences are limited for the best bathing practices, especially the skin health performance of cleansing products on children's atopic dermatitis skin. Methods: A randomised controlled clinical study was conducted in China among 4‐ to 18‐year‐old children with mild‐to‐moderate atopic dermatitis to evaluate the skin health effect of three cleansing systems (a mild synthetic bar, an ultra‐mild body wash with lipids, and an ultra‐mild body wash with lipids and zinc pyrithione) by measuring SCORing of Atopic Dermatitis (SCORAD), consumption of topical corticosteroid and the characteristics of microbiome. Results: Increased Staphylococcus aureus abundance and decreased microbial diversity were observed in atopic dermatitis lesion sites compared with healthy control sites. After 4 weeks of treatment, all three treatments showed clinically important improvement from baseline in SCORAD. Four‐week corticosteroid consumption was significantly lower for the two body wash groups than the bar group. A significant decrease in S. aureus abundance and increase in microbial diversity were observed in the lesion sites for the two body wash formulas, while the microbial diversity was statistically insignificant for the mild cleansing bar group. However, there were no incremental benefits provided by the body wash formulas based on the assessment of SCORAD. Conclusions: These results demonstrated the safety and efficacy of using the investigational body wash formulas with lipids in reducing the needs for corticosteroid and improving the healthy composition of skin microbiome vs. the mild synthetic bar soap.